Investigating Human Nature and Communication through Robots - Hideyuki Nakanishi (Frontiers Research Topics, 2017)
The development of information technology enabled us to exchange more items of information among us no matter how far we are apart from each other. It also changed our way of communication. Various types of robots recently promoted to be sold to general public hint that these robots may further influence our daily life as they physically interact with us and handle objects in environment. We may even recognize a feel of presence similar to that of human beings when we talk to a robot or when a robot takes part in our conversation. The impact will be strong enough for us to think about the meaning of communication. This e-book consists of various studies that examine our communication influenced by robots. Topics include our attitudes toward robot behaviors, designing robots for better communicating with people, and how people can be affected by communicating through robots.